Nationwide investigation of eukaryotic pathogens in ticks from cattle and sheep in Kyrgyzstan using metabarcoding - Singeun Oh; Nathalie Amvongo-Adjia; Hyun Jung Kim; Jun Ho Choi; Xavier Chavarria; Myung-hee Yi; Arwa Shatta; Bekbolsun Aknazarov; Ju Yeong Kim; Jung-Won Ju (PLoS ONE, 2025)
Ticks are significant vectors of bacterial, viral, and protozoan pathogens, impacting both public health and agriculture. In Kyrgyzstan, tick-borne diseases are a growing concern for livestock and human health. While bacterial and viral pathogens are widely studied, and limited previous investigations have focused on specific Babesia and Theileria species in certain host animals, comprehensive data on tick eukaryotic microbiota and potential pathogens across diverse hosts nationwide is scarce. To address this gap, our study provides the comprehensive nationwide assessment of the potential protozoan pathogens in ticks from cattle and sheep, analyzing data of Babesia and Theileria at the genus level. We collected 472 tick samples from cattle and sheep across seven regions of Kyrgyzstan (March-July 2022). Tick species were identified via microscope and Sanger sequencing (mitochondrial COI gene). Eukaryotic microbiota was analyzed using 18S rRNA V9 NGS. Sanger sequencing identified five genera and 11 tick species. NGS analysis revealed Babesia (13.3%) and Theileria (12.7%) as among the most prevalent protozoa detected at the genus level. Babesia was significantly more prevalent in nymph-stage ticks and those collected from sheep, whereas Theileria was detected across a broader range of tick species and host animals, showing less variation across life stages. No significant differences in prevalence were observed based on tick sex or the number of hosts in the tick life cycle. Regionally, Babesia detection was highest in the Osh region, particularly in ticks collected from both cattle and sheep. This is the first comprehensive nationwide analysis of tick eukaryotic metabarcoding study in Kyrgyzstan focusing on pathogenic protozoa detected at the genus level. Findings provide crucial baseline data on Babesia and Theileria geographic and host-specific prevalence. Understanding these information is essential for advancing future research and supporting the development of effective surveillance and control strategies against babesiosis and theileriosis in regional livestock.